2023
DOI: 10.3389/fpubh.2023.1149719
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic risk factors attributed burden in Iran at national and subnational levels, 1990 to 2019

Abstract: IntroductionMetabolic risk factors (MRFs) predispose populations to a variety of chronic diseases with a huge burden globally. With the increasing burden of these risk factors in Iran, in this study, we aimed to report the estimated burden attributed to MRFs at national and subnational scales in Iran, from 1990 to 2019.MethodsBased on the comparative risk assessment method of the Global Burden of Disease (GBD) Study 2019, data of deaths and disability-adjusted life years (DALYs) attributable to four top MRFs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…21 In addition, a study conducted in Iran showed that having a high body mass index was one of the largest contributors to musculoskeletal pain. 22 This finding may be one of the reasons why Iran has a high neck pain burden. Having a history of smoking has also been found to be related to impairment of the musculoskeletal system, lower bone marrow density, 23 as well as higher instances of lower back pain, 24 as well as neck pain.…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition, a study conducted in Iran showed that having a high body mass index was one of the largest contributors to musculoskeletal pain. 22 This finding may be one of the reasons why Iran has a high neck pain burden. Having a history of smoking has also been found to be related to impairment of the musculoskeletal system, lower bone marrow density, 23 as well as higher instances of lower back pain, 24 as well as neck pain.…”
Section: Discussionmentioning
confidence: 99%